Synthesis and characterization of hypercrosslinked hydroxyl functionalized co-polymer beads - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (European Polymer Journal, 2014)
Hydroxyl functionalized beaded copolymers were synthesized from 2-hydroxy ethyl methacrylate by suspension polymerization using two different crosslinking agents (EDMA, DVB) and diluents (1,1,2,2-tetrachloroethane, 1,2-dichlorobenzene). Microporous beads with high surface area were successfully synthesized and characterized by different techniques. Maximum surface area obtained was 564 m(2)/g bearing uniform, spherical as well as non-aggregation images of beads. Thermal properties such as DTG and DSC reveal that, type of crosslinker (flexible/rigid) is major while its concentration is minor parameter that affect decomposition and softening temperature of copolymer. Swelling ratio of copolymer beads was examined as a function of crosslinker and crosslink density. Swelling behavior is in accordance with copolymer-solvent interaction parameter. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Copolymer; Morphology; surface area; Suspension polymerization; Swelling ratio

Design and synthesis of cauliflower-shaped hydroxyl functionalized core-shell polymer - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Designed Monomers and Polymers, 2015)
Conventional crosslinked polymers and homopolymers both have their own limitations. As a result, core-shell polymer was synthesized to obtain cauliflower-shaped and highly hydroxyl functionalized polymer. For the core, acrylate-based copolymers were synthesized by varying crosslinkers and porogens at different crosslink density. Owing to high surface area (554 m(2)/g), poly(MMA-co-DVB) was used as a core and low-molecular weight (24,600g/mol) poly(GMA) was used as a shell in core-shell approach. Average particle sizes of the core polymers were in the range of 15-75 mu m. In order to evaluate reactivity efficiency of core-shell polymer, hydroxyl content was evaluated with a value of 3.97mmol/g. Importantly, hydroxyl content demonstrated the successful increase in reactive sites of the core-shell polymer over conventional crosslinked hydroxyl polymer. Notably, synthesized core-shell polymer has more surface area and pore volume which substantially attributes for better polymer efficiency during application. Scanning electron microscopy images revealed the spherical, uniform, and slightly conglomerated properties of core-shell polymer. Due to higher reactivity, insolubility, and more surface area of hydroxyl functionalized core-shell polymer, its use become inevitably essential.
Keywords: C-13 solid state NMR; cauliflower-shaped porous beads; core-shell polymer; hydroxyl functionalization; surface area

Hyperhydrophilic three-dimensional crosslinked beads as an effective drug carrier in acidic medium: adsorption isotherm and kinetics appraisal - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (New Journal of Chemistry, 2015)
Conventional drug delivery materials are known to provide slow and low drug loading in aqueous medium due to the hydrophobic or less hydrophilic properties of the carrier. However, the present study explored the synthesis of cheaply available metals modified with a hyperhydrophilic polymer. Hyperhydrophilic three-dimensional crosslinked beads as a drug carrier were synthesized with desirable properties that substantially influence the polymer efficiency. These synthesized polymers were characterized for surface area, particle size, acid content and morphology, and the metal modification was evaluated to obtain an efficient polymer for drug adsorption in an acidic medium. Contact time, which significantly affects drug adsorption was comparatively evaluated using the cheaply available metals, cobalt and nickel. Interestingly, an adsorption study revealed that gradual drug loading occurs during the initial 12 h. Afterwards, adsorption increases steadily and then stabilizes. Furthermore, theoretical predictions of adsorption, including Langmuir adsorption isotherm and pseudo order kinetics, were also evaluated. Remarkably, polymer supported Co/Ni demonstrated 85 and 78% metoprolol drug adsorption, respectively, at an optimum pH of 3 after 24 h. Langmuir adsorption isotherm revealed monolayer adsorption on the polymer supported Co/Ni. Pseudo first and second order kinetics were also evaluated and demonstrated the adsorption mechanism and equilibrium adsorption capacity, respectively.

Role of interfacial tension of solvating diluents and hydrophilic-hydrophobic cross-linkers in hyper-cross-linked solid supports - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Industrial & Engineering Chemistry Research, 2015)
The properties of a hyper-cross-linked solid support are the outcome Of the interfacial tension created by solvating/nonsolvating diluents, the hydrophilicity/hydrophobicity of the cross-linkers, and their concentrations. Interestingly, a More hydrophobic diluent and cross-linker as well as a higher concentration of cross-linker-containing copolymer revealed an increase In surface area. A high surface area and low cross-link density (CLD) polymer illustrated higher epoxy content. Importantly, maximum surface area (533 m(2)/g) Was obtained at high CLD; inversely, epoxy,content (1.83 mmol/g) was higher at low CLD polymer. Notably, greater rigidity of cross-linker and its higher concentration increased T-max and T-g; contrarily, greater flexibility of cross-linker and its concentration attenuated T-max and T-g. Thermal study demonstrated the thermostability (300 degrees C) and polymer safe temperature (220 degrees C). Indeed, a lower solubility parameter difference between polymer and swelling solvent produces a higher polymer-solvent interaction parameter, resulting in increased polymer swelling. Polymers with high surface area and low CLD demonstrated greater swelling behavior.

Synthesis and characterization of thermotropic liquid crystalline polyimides - Mane, Sachin; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Bulletin of Materials Science, 2015)
Non-symmetrical and linear dyad-based mesogens were synthesised containing imine or ester bridging group. In the present work, due to the absence of branching in diamine-based mesogen, the structure has-rigidity inversely imine/ester bridging groups between two benzene rings imparts-flexible property to the mesogen and consequently rigid-flexible property has been balanced. The synthesised mesogens were characterized by different techniques including nuclear magnetic resonance and Fourier transform infrared spectroscopy. Liquid crystalline polymers (LCPs) were synthesised using pyromellitic dianhydride and 4-[(4-aminobenzylidene)amino]aniline or 4-aminophenyl-4-aminobenzoate. Subsequently, thermotropic liquid crystalline polymers (TLCPs) have also been evaluated to obtain optical microscopy textures at different temperatures which demonstrated interesting and notable changes. It is worth noting that marble-like textures were observed upto 200A degrees C.
Keywords: Diamine; liquid crystalline polymer; mesogen; optical microscopy textures; pyromellitic dianhydride

Crosslinked polymer embedded Cu/Ag for comparative drug adsorption and kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal of Polymeric Materials and Polymeric Biomaterials, 2016)
Two-dimensional crosslinked polymer (2-DCP) was synthesized for evaluation of drug adsorption and kinetics thereof. Further, polymer properties were evaluated and parameters such as contact time and adsorption isotherm were also studied. Herein, contact time demonstrated 83% and 85% of drug loading in an acidic medium for two-dimensional crosslinked polymer embedded copper and silver (2-DCP-Cu/Ag), respectively in 24h. Initial 4h is the exponential drug loading period whereas drug loading was increased gradually after 4h. Salbutamol loading was well-fitted to Langmuir adsorption isotherm, which indicated a monolayer drug adsorption with respect to 2-DCP-Cu/Ag. Pseudo first- and pseudo second-order kinetics was evaluated to perceive the drug adsorption mechanism and equilibrium adsorption capacity. Monolayer drug adsorption with chemisorption mechanism was observed for 2-DCP-Cu/Ag. In addition to this, decomposition temperature of polymer was 440 and 325 degrees C while glass transition temperature of polymer was 280 and 200 degrees C before and after metal modification, respectively. (A=aqueous phase; B=organic phase; C=drug solution; D=drug loaded polymer; E=enlarged drug loaded polymer.) [GRAPHICS] .
Keywords: Adsorption isotherm; adsorption kinetics; crosslink polymer; drug loading; langmuir adsorption isotherm; salbutamol

Interfacial tension approach toward drug loading with two-dimensional crosslinked polymer embedded gold: adsorption kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal Of Polymeric Materials And Polymeric Biomaterials, 2016)
Interfacial tension of drugs with hydrophilic polymer (A) embedded gold resulting into selective drug adsorption, which also affected the drug adsorption kinetics. Two-dimensional crosslinked polymer embedded gold was synthesized for drug loading application in an acidic buffer. Lower interfacial tension of pantoprazole sodium (B) revealed the exponential loading inversely loading was gradual for chloroquine (C) having more interfacial tension with adsorbent. Initial 2 h was the exponential adsorption period for a pantoprazole sodium whereas exponential adsorption begins after 12 h for a chloroquine. Monolayer drug adsorption was obtained because Langmuir adsorption isotherm was obeyed by both drugs. Moreover, pseudo first-and pseudo second-order kinetics was also evaluated which demonstrated that reactive sites of the adsorbent are homogeneous and drug adsorption mechanism is chemisorption and not the physisorption. Thermal analysis was evaluated to confirm the polymer thermostability and glass transition temperature during catalytic applications in thermal reactions.
Keywords: Adsorption isotherm; adsorption kinetics; drug loading; drug polarity; Interfacial tension

Racemic drug resolution: a comprehensive guide - Mane, Sachin (Analytical Methods, 2016)
The human body is amazingly chirally selective, and consequently enantiopure drugs are essential for treating disease. Nearly 50% of drugs are chiral wherein pharmacological activity resides with the eutomer (pharmacologically active enantiomer) whereas the distomer (inactive/less potent/equally potent/different pharmacological activity/toxic enantiomer) metabolizes by a different pathway and creates unnecessary burden on the body. A teratogenic (toxic) isomer in a racemic drug creates sideeffects, genetic diseases, or may cause death in the case of high dosage. Nowadays, market approval of enantiopure drugs has increased exponentially whereas it has tremendously decreased for racemic and achiral drugs. An expensive process is the main drawback in obtaining enantiopure drugs. Different methods such as chromatography, spectroscopy, and thermal analysis are available for optical purity determination. However, only a few chromatographic methods are useful on an industrial scale. In the present review, racemic resolution and optical purity determination methods are discussed with examples. In addition to this, eutomers and distomers of different drugs containing a single chiral center are also reported.

Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties

Selective solid-phase extraction of metal for water decontamination - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Applied Polymer Science, 2016)
Metal-contaminated industrial effluent is a major concern for human health. Therefore, the removal of metal is of primary importance. In this study, metals were selectively extracted from water. Selective metal recovery was studied with a crown-ether-based polymer, wherein the selectivity was observed for strontium over lead. Parameters influencing the metal recovery, such as the contact time, adsorbent dosage, and metal-ion concentration, were evaluated. Interestingly, the adsorption rate of strontium was exponentially increased for the initial 4 h, and lead was adsorbed exponentially after 6 h. Notably, 98% strontium adsorption and 64% lead adsorption were obtained in 24 h. The Langmuir adsorption isotherm was in good agreement and demonstrated that the reactive sites of the adsorbent were homogeneous with monolayer metal adsorption with an adsorbent. The Freundlich adsorption isotherm was not obeyed by both metals. The pseudo-first-order and pseudo-second-order kinetics indicated that strontium was adsorbed by chemisorption and lead was adsorbed by physisorption. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42849.
Keywords: Adsorption; copolymers; crosslinking; kinetics; radical polymerization